2017
DOI: 10.1038/ismej.2017.83
|View full text |Cite
|
Sign up to set email alerts
|

Co-evolution with Staphylococcus aureus leads to lipopolysaccharide alterations in Pseudomonas aeruginosa

Abstract: Detrimental and beneficial interactions between co-colonizing bacteria may influence the course of infections. In cystic fibrosis (CF) airways, Staphylococcus aureus prevails in childhood, whereas Pseudomonas aeruginosa progressively predominates thereafter. While a range of interactions has been identified, it is unclear if these represent specific adaptations or correlated responses to other aspects of the environment. Here, we investigate how P. aeruginosa adapts to S. aureus by evolving P. aeruginosa in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 44 publications
4
83
1
Order By: Relevance
“…AMP, ATM, and CAR are all substrates of MexAB-OprM but, as mentioned above, correcting the oprM defect in Z61 shifted susceptibility to all three compounds by 16-fold but did not bring susceptibility back to near parental levels (Z61-CDY0025, Table 1), and deleting oprM in the parent NB52041 strain caused a 16-fold decrease in susceptibility to ATM and CAR but only a 2-fold shift for AMP (NB52041-CDY0175, Table 2). The impact of pump deletion alone on AMP activity in the absence of inhibition of AmpC was previously reported to be only ϳ2-fold in PAO1 (25), which is presumably related to the interplay of AmpC and MexAB-OprM when both factors effectively act on the ␤-lactam (23). This differential impact of the oprM defect on ATM and CAR compared to AMP therefore suggested that a specific defect in the chromosomally encoded AmpC ␤-lactamase existed in Z61.…”
Section: Resultsmentioning
confidence: 99%
“…AMP, ATM, and CAR are all substrates of MexAB-OprM but, as mentioned above, correcting the oprM defect in Z61 shifted susceptibility to all three compounds by 16-fold but did not bring susceptibility back to near parental levels (Z61-CDY0025, Table 1), and deleting oprM in the parent NB52041 strain caused a 16-fold decrease in susceptibility to ATM and CAR but only a 2-fold shift for AMP (NB52041-CDY0175, Table 2). The impact of pump deletion alone on AMP activity in the absence of inhibition of AmpC was previously reported to be only ϳ2-fold in PAO1 (25), which is presumably related to the interplay of AmpC and MexAB-OprM when both factors effectively act on the ␤-lactam (23). This differential impact of the oprM defect on ATM and CAR compared to AMP therefore suggested that a specific defect in the chromosomally encoded AmpC ␤-lactamase existed in Z61.…”
Section: Resultsmentioning
confidence: 99%
“…The parallel evolution of mutations in four genes associated with O antigen biosynthesis within and between populations strongly suggests that the outer membrane may be altered in response to TOB and biofilm selection in P. aeruginosa (Burrows et al, 1996; Tognon et al, 2017; Wong et al, 2012). Experiments in strain PAO1 have shown that loss of B band O antigen is associated with aminoglycoside resistance by increasing impermeability and reducing binding affinity to the outer membrane (Bryan et al, 1984; Kadurugamuwa et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Since this state of coexistence is apparently solely attributable to P. aeruginosa , the selective advantage for P. aeruginosa leads to questions. Indeed, previous studies showed that cocultivation with S. aureus induces LPS mutation in P. aeruginosa associated with fitness gain and antibiotic resistance 41 , and that S. aureus exoproducts restore and enhance P. aeruginosa motility 32 . The state of coexistence could thus represent a trade-off allowing both pathogens to benefit mutually and maintain equilibrium.…”
Section: Discussionmentioning
confidence: 99%